Drug Use Stigma and Public Preferences for Public Health Versus Legal System Responses - Kort-Butler, Lisa A. (Journal of drug issues, 2025)
This study explored what perceptions and beliefs about substances and substance users, personal experiences, and network experiences with substance use were related to people’s preferences for public health and legal system responses to substance use. Social context was also considered, including location of residence, political ideology, and a sense of insecurity. Data were from the Nebraska Annual Social Indicators Survey, a cross-sectional omnibus mail survey of public attitudes in Nebraska, conducted in fall 2021. Approximately 1700 adults completed the survey. Controlling for demographic characteristics, the study found stigmatized attitudes about substance use, limited or no personal history with substance use, rural residence, and political conservatism were associated with more support for legal system responses. In contrast, less stigmatized attitudes about substance use, personal history of marijuana use, urban residence, political liberalism, and a sense of security were all associated with more support for public health responses.